Pulse transit time - reliable marker for sleep disturbances among athletes - Rankov, K. (Journal of Applied Sports Sciences, 2019)
Sleep is essential for everyone and is important for the normal human functioning. Lack of sleep, called sleep deprivation, is a condition leading to poor sports training and achievements. Different factors contribute to sleep deprivation among athletes. Respiratory sleep disorders such as Upper airway resistance syndrome (UARS) and Obstructive Sleep Apnea (OSA) are factors that rebound most to sleep deprivation for certain groups of athletes such as wrestlers, judokas and sumo wrestlers.The present study investigates the UARS and OSA occurrence in the above mentioned groups of athletes using Pulse Transit Time (PTT) as an early noninvasive indicator of respiratory effort and sympathetic nervous system activity.Sixty-seven elite athletes, practicing wrestling, sumo wrestling and judo were screened by enquiry for sleep breathing disturbances. The study involved the most suspicious ten cases for sleep-disordered breathing symptoms. They underwent full standard polysomnographic (PSG) examination using Alice 5 System Philips - Respironics Inc. with the registration of PTT.Among all athletes, regardless of the presence of changes in hemoglobin saturation or apnea-hypopnea index changes (AHI), a significant drop in the PTT value with more than 8-15 ms for sleep stages N1 and N2 (p<0.005) was observed, as well as with more than 6-8 ms for sleep stage N3 (p<0.005). We found bigger dependence of PTT by Arousal Index (ArI) than AHI and Desaturation Index (DI). Therefore, PTT can be used as a good indicator of sleep fragmentation before the development of the clinical picture of UARS and OSA.As a good indicator for inspiratory effort and sympathetic changes in UARS and OSA, PTT gives an opportunity for early diagnosis of respiratory sleep disorders among athletes. Prevention, timely detection and appropriate treatment of sleep disorders before the development of their full clinical picture will improve the processes of recovery and performance in sports practice